The influence of person-environment fit, person-organisation fit and person-job fit on career satisfaction and intention to leave among university academics - Sebolaoa, Refiloe Engelina (Vaal University of Technology, 2020)
The face of South African (SA) universities’ academic environment has changed over the past decade, primarily propelled by transformation issues, new policies and practices, which also required academics to have certain skills and attributes. Recruiting and retaining key academics in the public higher education (HE) are not once-off events; they are ongoing processes that involve analysing the needs, culture and practices of the organisation and identifying individuals whose skills and personalities better meet those organisational needs. Given the rapid restructuring and transformation of SA public HE, recruiting and retaining of essential talent has been a huge challenge experienced by higher education institutions (HEIs). Research relating to how HEIs could better attract and retain key talent has, however, been scarce; as such, this study aims to fill the existing gap in the literature. Against this background, this study aimed at exploring the influence of person-environment fit (PEF), person-organisation fit (POF) and person-job fit (PJF) on career satisfaction (CS) and the influence of CS on intention to leave (ITL) among university academics. Embedded within a positivist paradigm, the study followed a quantitative research approach. A structured questionnaire was used to measure study constructs. In addition to the soliciting information on the demographic variables, respondents were requested to complete five different measuring scales, namely the general environment fit scale (GEFS), organisational culture profile (OCP), the knowledge, skills and ability profile (KSAP), the career satisfaction scale (CSS) and the intention to leave scale (ITLS). A total of 550 questionnaires were distributed to the identified sample of university academics and from that distribution only 202 questionnaires were used for data analysis. Descriptive statistics techniques as well as correlation and regression analysis were used to evaluate academics’ perceptions and relationships between study constructs. Findings revealed the existence of strong positive associations between the three fit constructs and CS and a negative association between CS and ITL. The findings also propose that the HEI could use fit dimensions to increase the level of academics’ CS and reduce their proclivity to leave the HEI. Academics’ CS can be enhanced by the implementation of a career advancement policy that will ensure that academics are provided with fair and equal training and development opportunities and are promoted based on their individual performances. To constantly reduce the propensity to leave the institution, the HEI could continuously satisfy career goals of academics through the provision of career progression opportunities.
M. Tech. (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Person-environment fit; Person-job fit; Person-organisation fit; Career satisfaction; Intention to leave; University academics; Higher education institution; Dissertations, Academic -- South Africa.; Job satisfaction -- South Africa.; Education, Higher -- South Africa.